Validation of Mobile Artificial Intelligence Technology–Assisted Dietary Assessment Tool Against Weighed Records and 24-Hour Recall in Adolescent Females in Ghana - Folson, Gloria; Bannerman, Boateng; Atadze, Vicentia; Ador, Gabriel; Kolt, Bastien; McCloske, Peter; Gangupantulu, Rohit; Arrieta, Alejandra; Braga, Bianca C.; Arsenault, Joanne; Kehs, Annalyse; Doyle, Frank; et al. (Elsevier, 2023)
Background Important gaps exist on dietary intake of adolescents in low- and middle-income countries (LMICs), partly due to expensive assessment methods and inaccuracy in portion size estimation. Dietary assessment tools leveraging mobile technologies exist but few have been validated in LMICs.